2023
DOI: 10.1128/mbio.01297-23
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of regulator on virulence plasmid of hypervirulent Klebsiella allows bacterial lifestyle switch in response to iron

Abstract: Hypervirulent Klebsiella pneumoniae causes liver abscess and potentially devastating metastatic complications. The majority of Klebsiella -induced liver abscess are caused by the CG23-I sublineage of hypervirulent Klebsiella pneumoniae . This and some other lineages possess a >200-kb virulence plasmid. We discovered a novel protein IroP nestled in the virulence plasmid-encoded salmochelin operon that cross-regulates and suppresses the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 84 publications
1
5
0
Order By: Relevance
“…A recent report has suggested that the coexistence of c-rmpA with p-rmpA and p-rmpA2 increases the lethality of K1 K. pneumoniae strains and the development of hepatic abscesses more than the coexistence of siderophores. 74 Each virulence factor present in K. pneumoniae participates in the infectious process depending on external signals, as in the case of the recently described iroP switch, 75 where iron favors biofilm formation in iron-rich environments such as the intestine while reducing capsule production. Therefore, in our virulence model, the capsule becomes highly relevant as a mechanism used by hvKP strains to evade phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report has suggested that the coexistence of c-rmpA with p-rmpA and p-rmpA2 increases the lethality of K1 K. pneumoniae strains and the development of hepatic abscesses more than the coexistence of siderophores. 74 Each virulence factor present in K. pneumoniae participates in the infectious process depending on external signals, as in the case of the recently described iroP switch, 75 where iron favors biofilm formation in iron-rich environments such as the intestine while reducing capsule production. Therefore, in our virulence model, the capsule becomes highly relevant as a mechanism used by hvKP strains to evade phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Each virulence factor present in K. pneumoniae participates in the infectious process depending on external signals, as in the case of the recently described iroP switch, where iron favors biofilm formation in iron-rich environments such as the intestine while reducing capsule production. Therefore, in our virulence model, the capsule becomes highly relevant as a mechanism used by hvKP strains to evade phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a phenotypic switch between type III fimbriae and the hypermucoviscous capsule in response to iron levels has been reported in the SGH10 strain. 70,27 The iron-regulated outer membrane protein IroP, encoded in the virulence plasmid, inhibits the expression of the mrk operon under low iron conditions, promoting biofilm formation. Since polyphosphates (polyP) are directly involved in intracellular iron homeostasis 74 , the observed alterations in the capsule and biofilm might be related to this recently described phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of K. pneumoniae and polyP metabolism, the effect of gallein, an inhibitor of polyP synthesis, has been studied, revealing a concentration-dependent decrease in biofilm formation 26 . hvKP strains are associated with enhanced virulence and have been observed to form biofilms and produce a protective capsule, contributing to their pathogenicity 27 . However, the precise mechanism by which polyP metabolism and PPK1 influence Klebsiella virulence remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…It could also be that in these strains, T3F is regulated differently. In the specific case of hypervirulent strains, characterized by the presence of the virulence plasmid encoding rmpA , but also other siderophores like salmochelin ( iro operon) and aerobactin ( iuc operon), it was recently shown that T3F and capsule are both tightly regulated by iroP also present in the virulence plasmid (Chu et al 2023 ). IroP acts as a switch, by which T3F is repressed during capsule expression.…”
Section: Discussionmentioning
confidence: 99%